MODERN DEVELOPMENT AND IMPROVEMENT OF THE PERSONAL AND PROFESSIONAL QUALITY OF A COMPUTER SCIENCE TEACHER - Gulchekhra Yuldashovna Yusupova (Journals Park Publishing, 2023)
The diversity and complexity of the postmodern era poses new and important challenges for teacher education. There is a need to better understand and recognize the crucial role of personal dispositions in vocational training. Teacher training programs should focus more on goals such as the development of conflict literacy, self-awareness, empathy, leadership and collaboration skills, that is, taking into account not only the cognitive, but also the social and emotional aspects of human development. In this article, educators describe what they consider to be the competencies and qualities required of future teachers and provide a starting point for a broader discussion about the crucial role of beliefs and emotions in being and becoming a teacher. The questions raised here should contribute to a better understanding of what it means to be a teacher and therefore lead to better planning of teacher training programs.
Keywords: competencies, learning emotions, personal development, professional development, teacher belief systems, teacher education, teacher training programs.